2015
DOI: 10.1096/fj.15-273722
|View full text |Cite
|
Sign up to set email alerts
|

Pannexin 3 is required for normal progression of skeletal development in vertebrates

Abstract: The vertebrate skeletal system has various functions, including support, movement, protection, and the production of blood cells. The development of cartilage and bones, the core components of the skeletal system, is mediated by systematic inter- and intracellular communication among multiple signaling pathways in differentiating progenitors and the surrounding tissues. Recently, Pannexin (Panx) 3 has been shown to play important roles in bone development in vitro by mediating multiple signaling pathways, alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 38 publications
4
42
0
Order By: Relevance
“…(), which includes many of the authors of the present study, and that of Oh et al. (). Our initial study using a global Panx3‐null mouse was focused on the role of Panx3 in the onset of osteoarthritis (Moon et al.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…(), which includes many of the authors of the present study, and that of Oh et al. (). Our initial study using a global Panx3‐null mouse was focused on the role of Panx3 in the onset of osteoarthritis (Moon et al.…”
Section: Discussionmentioning
confidence: 85%
“…Oh et al. () used a different global Panx3‐null mouse to study the effects of Panx3 on skeletal development, as compared with previously published in vitro studies (i.e. Iwamoto et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Panx3 is induced by Bone morphogenetic protein 2 (BMP2) and a target gene of Runt-related transcription factor 2 (Runx2), which is a key transcription factor for bone formation [17]. Panx3 knockout mice evidently demonstrated that Panx3 is essential for normal skeletal development [18, 19]. Thus, Panx3 plays a crucial role in hard tissue development.…”
Section: Introductionmentioning
confidence: 99%